2020
DOI: 10.3390/jcm9041232
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sugammadex on Post-Operative Pulmonary Complications in Laparoscopic Gastrectomy: A Retrospective Cohort Study

Abstract: The use of sugammadex can reduce post-operative residual neuromuscular blockade, which is known to increase the risk of post-operative respiratory events. However, its effect on post-operative pulmonary complications is not obvious. This study was performed to evaluate the effects of sugammadex on post-operative pulmonary complications in patients undergoing laparoscopic gastrectomy between 2013 and 2017. We performed propensity score matching to correct for selection bias. Post-operative pulmonary complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(39 citation statements)
references
References 37 publications
2
35
2
Order By: Relevance
“…Although sugammadex is well known for its use in reducing the risk of postoperative residual neuromuscular blockade in well-controlled studies, this has not always improved clinical measures of postoperative strength and has not always reduced postoperative pulmonary complications. 42,43 In daily clinical practice, the data regarding its impact on postoperative pulmonary complications have been mixed. 44 We observed a lower absolute incidence rate of postoperative pulmonary complications over time; however, we were simply unable to distinguish that from background improvements that we observed in our cohort.…”
Section: Risk Of Postoperative Pulmonary Complicationsmentioning
confidence: 99%
“…Although sugammadex is well known for its use in reducing the risk of postoperative residual neuromuscular blockade in well-controlled studies, this has not always improved clinical measures of postoperative strength and has not always reduced postoperative pulmonary complications. 42,43 In daily clinical practice, the data regarding its impact on postoperative pulmonary complications have been mixed. 44 We observed a lower absolute incidence rate of postoperative pulmonary complications over time; however, we were simply unable to distinguish that from background improvements that we observed in our cohort.…”
Section: Risk Of Postoperative Pulmonary Complicationsmentioning
confidence: 99%
“…Sugammadex can quickly and e ciently re-establish normal muscle strength and cause less postoperative pleural effusion rate after TA-TAVI procedure. This nding was reinforced from a retrospective observational study by Han et al (17). They found that the postoperative pleural effusion rate was lower in patients receiving sugammadex when compared to patients receiving neostigmine, although they failed to found a signi cant difference of the incidence of PPCs between the groups (17).…”
Section: Discussionmentioning
confidence: 96%
“…This nding was reinforced from a retrospective observational study by Han et al (17). They found that the postoperative pleural effusion rate was lower in patients receiving sugammadex when compared to patients receiving neostigmine, although they failed to found a signi cant difference of the incidence of PPCs between the groups (17). Furthermore, previous study showed that neostigmine can adversely affect neuromuscular function and impair muscle function (genioglossus muscle and diaphragm) which was associated with respiratory complications (37,38).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Such continued residual paralysis may result in pulmonary complications such as pulmonary edema, atelectasis, aspiration, and pneumonia, leading to reintubation. Complete reversal of neuromuscular blockade may result in reduced postoperative pulmonary complications (23,24).…”
Section: Intraoperativementioning
confidence: 99%